Tetrandrine for Targeting Therapy Resistance in Cancer - Lima, Ellen N.; Lamichhane, Santosh; K. C, Pramod Bahadur; Ferreira, Elisa Silva; Koul, Sweaty; Koul, Hari K. (Current Topics in Medicinal Chemistry, 2024)
During the last five decades, there has been tremendous development in our understanding of cancer biology and the development of new and novel therapeutics to target cancer. However, despite these advances, cancer remains the second leading cause of death across the globe. Most cancer deaths are attributed to the development of resistance to current therapies. There is an urgent and unmet need to address cancer therapy resistance. Tetrandrine, a bis-benzyl iso-quinoline, has shown a promising role as an anti-cancer agent. Recent work from our laboratory and others suggests that tetrandrine and its derivatives could be an excellent adjuvant to the current arsenal of anti-cancer drugs. Herein, we provide an overview of resistance mechanisms to current therapeutics and review the existing literature on the anti-cancer effects of tetrandrine and its potential use for overcoming therapy resistance in cancer.
Keywords: Trail